Evaluation of biomass and its thermal decomposition products as fuels for direct carbon fuel cells. (November 2019) - Xu, Kai; Dong, Jizhou; Li, Xian; Wang, Junquan; Hu, Zhenzhong; Li, Aijun; Yao, Hong
Abstract: Direct carbon fuel cell (DCFC) with biomass as fuel is a promising power generation technology due to the high efficiency of DCFC system and renewability of biomass. This study aims to find the relationship of electrochemical performance between biomass and its thermal decomposition products, and also to reveal their degradation mechanisms during durability tests in solid oxide fuel cells. The thermochemical properties of biomass and biochar, the electrochemical behaviors of biomass, biochar and biogas were characterized comprehensively, and subsequently the degradation process of biomass, biochar and biogas fueled cells were analyzed. The results showed that raw biomass fueled cells produced considerable peak power density (PPD, 0.144 W cm −2 at 1123 K) but experienced rapid discharge degradation. Torrefaction pretreatment (573K) of raw samples compromised PPDs while pyrolysis pretreatment (973K) enhanced PPDs. The electrochemical performance of raw biomass was the combined electrochemical contribution of its decomposition products (biochar and biogas). With biochar as fuel, the power was generated from CO electro-oxidation and biochar-CO2 gasification. Feeding of CO2 into the anode chamber continuously did not improve the output performance. The discharge degradation was mainly caused by the gradually decreasing gasification reactivity of biochar with CO2 and slight anode carbon deposition. With biogas as fuel, the anode reactions were electro-oxidation of active species like H2, CO, CH4, and the cell degraded due to severe carbon deposition. Biomass, biochar and biogas fueled cells all suffered from anode carbon deposits, most of which were in the form of graphitic carbon. Highlights: Raw biomass delivered considerable but unstable electrochemical performance. Thermochemical and electrochemical conversion of biomass was studied and linked. Both biochar and biogas contributed greatly to cell output and degradation. Feeding of CO2 into the anode did not improve the output performance. Biochar fueled cell degraded due to decreasing char reactivity and C deposit.